- HubPages
*»* - Education and Science
*»* - Math

# How to solve algebra problems

## What is algebra?

Algebra is the use of letters or symbols in an equation to represent quantities or numbers. For example 3p+5p= 8p. With algebra terms must contain the same symbol or letter in order to be added or subtracted, this means that in an equation such as 3w+2t-4t+2w, 3w and 2t can not be added but first rearrange grouping the w's together and the t's together, such as 3w+2w-2t-4t then you can add the like terms and the result would be 5w-2t. However equations do not have to contain the same letter or symbol in order to be multiplied or divided.

This is the basics of algebra now i will go through a work sheet with you which would help you to understand algebra alot better. This will help with any homework help you needed in the subject area algebra.

## Algebra Problems

Now we will go true five (5) algebra problems where we would simplify the equations. The equations are shown in the photo to the right labeled algebra problems.

a)6a is the answer because 3*2 is 6 and the 'a' will remain the same

b)20b is the answer because 5*4=20 and 'b' remains the same

c)12ab is the result because 4*3 =12 and the 'ab' goes behind the number

now you should have gotten the drift

d)14a^{²}

e)24bc

## Homework help with algebra problems

Find the value of each expressions in the photo to the right labeled homework help.

a)5(2) +7(3) +2(4)

=10 + 21 + 8

=39

b)2(2) × 3 (3) × 4

=4 × 9 × 4

=44

c)5(2)(3)(2)

=60

d)2²3

=12

## Removing brackets

When doing removing brackets in algebra you must multiply each term inside the brackets by the term outside of the brackets. Thus removing the brackets.

For example:

3(a+2b+5c)

=3a+6b+15c

Now lets do a little exercise with removing brackets. The exercise is shown in the figure to the right labeled homework help 1.

a)2×a+2×b

=2a+2b

b)3×x+3×2y

=3x+6y

c)4×3p+4×5q

=12p+20q

d)5a×b+5a×c

5ab+5ac

## Removing brackets and simplify

Example:

x(x² - 1) +x²(x+2) - x(5-x²)

=(x×x² - x×1) +(x²×x+x²×2) - (x×5 -x×x²)

=x³-x+x³+2x²-5x-x³

=x³+x³-x³+2x²-x-5x <-----Group the like terms together

=x³+2x²-6x

Another exercise on removing brackets and simplify the exercise is shown to the right in the photo labeled removing brackets and simplify.

a) 3×x + 3×y+2×x-2×y

=3x+3y+2x-2y

=3x+2x+3y-2y

=5x+y

b)4×x+4×y+3×2x+3×5y

=4x+4y+6x+15y

=4x+6x+4y+15y

=10x+19y

## Comments

No comments yet.